Electromagnetic surface waves at exceptional points. (14th December 2020) - Lakhtakia, Akhlesh; Mackay, Tom G; Zhou, Chenzhang
Abstract: Guided by the planar interface of two dissimilar linear, homogeneous mediums, a Voigt surface wave arises due to an exceptional point of either of the two matrixes necessary to describe the spatial characteristics in the direction normal to the planar interface. There is no requirement for either or both partnering mediums to be dissipative, unlike a Voigt plane wave which can propagate only in a dissipative (or active) medium.